2013
DOI: 10.1002/cplu.201300247
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Co–Mn Oxide‐Catalysed Selective Aerobic Oxidation of Vanillyl Alcohol to Vanillin in Base‐Free Conditions

Abstract: Manganese‐doped cobalt mixed oxide (MnCo‐MO) catalyst was prepared by a solvothermal method. The as‐prepared catalyst was characterised by X‐ray photoelectron spectroscopy, H2 temperature‐programmed reduction, O2 temperature‐programmed oxidation and XRD. This catalyst gave 62 % conversion with 83 % selectivity to vanillin in 2 hours for the liquid‐phase air oxidation of vanillyl alcohol without using base. Three different types of metal oxides were observed in the prepared catalyst, which could be identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 43 publications
2
47
0
Order By: Relevance
“…68,86 The use of a manganese-doped cobalt mixed oxide catalyst prepared by a solvothermal method was proposed in the oxidation of vanillyl alcohol to vanillin without using a base. 87 Three different types of metal oxides were observed in the prepared catalysts, which could be identified as Co 3 O 4 , Mn 3 O 4 and CoMn 2 O 4 . Among these, the tetragonal phase of CoMn 2 O 4 was found to be the most active and selective for vanillyl alcohol oxidation.…”
Section: Oxidation Of Alcohols Using Single-metal and Alloy Catalystsmentioning
confidence: 99%
“…68,86 The use of a manganese-doped cobalt mixed oxide catalyst prepared by a solvothermal method was proposed in the oxidation of vanillyl alcohol to vanillin without using a base. 87 Three different types of metal oxides were observed in the prepared catalysts, which could be identified as Co 3 O 4 , Mn 3 O 4 and CoMn 2 O 4 . Among these, the tetragonal phase of CoMn 2 O 4 was found to be the most active and selective for vanillyl alcohol oxidation.…”
Section: Oxidation Of Alcohols Using Single-metal and Alloy Catalystsmentioning
confidence: 99%
“…Figure shows conversion/selectivity (%) values with respect to time obtained in the Ru/ n ‐HT catalyzed aerobic oxidation of cinnamyl, vanillyl and veratryl alcohols, we found that Ru/ n ‐HT provided turnover frequency (TOF; TOF=mol of product/mol of ruthenium×time and all TOF values given here are not corrected to for the number of exposed surface atoms; that is, the values given are lower limits) values of 13.2, 5.1 and 11.4 h −1 for the aerobic oxidation of cinnamyl, vanillyl and veratryl alcohols, respectively. These TOF values are notably higher than those of obtained by Bi−Pt/Al 2 O 3 (2.1 h −1 for (1)), Pd/SWCNT (0.7 h −1 for (1)), MnFe 1.5 Ru 0.35 Cu 0.15 O 4 (7.9 h −1 for (1)), Au/CeO 2 (1.2 h −1 for (1)), CoMn 2 O 4 (3.1 h −1 for (2)), Co 3 O 4 (2.8 h −1 for (2)), Ru/Al 2 O 3 (1.8 h −1 for (3)), Ru/SiO 2 (1.6 h −1 for (3)), and Ru/ZIF‐8 (1.9 h −1 for (3)) catalysts tested in the aerobic oxidation of same substrates.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, cinnamyl, vanillyl and veratryl alcohols are most widely used lignin model compounds to mimic the propyl side‐chain (cinnamyl alcohol), phenolic (vanillyl alcohol) and non‐phenolic (veratryl alcohol) functional groups of lignin . Up to date, various enzymatic,, homogeneous, and heterogeneous catalytic systems have been developed and tested in the aerobic oxidation of these lignin model compounds. Despite the improvements made by the enzymatic catalysis, these systems usually suffer from low stability, pH adjustments and enzyme deactivation and these concerns limit their usability.…”
Section: Introductionmentioning
confidence: 99%
“…The oxygen concentration at the interface of the gas-liquid phase can be calculated by Henry's Law directly (Equation (15)). Thus, Equations (12)(13) were derived based on the assumptions above.…”
Section: Kinetic Parametersmentioning
confidence: 99%
“…During the reaction process, less than 0.5 g solvent was detected in gas absorption equipment 15 (Figure 1), demonstrating no reactant leakage. The intrinsic kinetic constants k 21 and k 22 were derived by nonlinear regression of Equations (12)(13). The Hatta numbers satisfied the pseudo-first order reactions well for both steps of the consecutive reactions (Tables 1 and 2).…”
Section: Kinetic Parametersmentioning
confidence: 99%